2003
DOI: 10.1016/s0020-7292(02)00374-0
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal color Doppler ultrasonography for prediction of pre-cancerous endometrial lesions

Abstract: Doppler's velocity waveforms of uterine vessels coupled with transvaginal ultrasonography are not valuable enough to replace histopathological examination in the diagnosis of a neoplastic endometrial pathology. However, it may be helpful in cases in which invasive techniques are difficult to perform and in the differentiation of a certain group of patients at little risk of endometrial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…Other researchers concluded that Doppler's velocity waveforms of uterine vessels performed with TVS are not beneficial enough to replace histopathological examination in the diagnosis of a neoplastic endometrial pathology. Nevertheless, it may be helpful in cases in which invasive procedures are difficult to perform and in the differentiation of a certain group of women less likely to develop endometrial carcinoma [19]. The results of the current study are promising.…”
Section: Discussionmentioning
confidence: 74%
“…Other researchers concluded that Doppler's velocity waveforms of uterine vessels performed with TVS are not beneficial enough to replace histopathological examination in the diagnosis of a neoplastic endometrial pathology. Nevertheless, it may be helpful in cases in which invasive procedures are difficult to perform and in the differentiation of a certain group of women less likely to develop endometrial carcinoma [19]. The results of the current study are promising.…”
Section: Discussionmentioning
confidence: 74%
“…However, with the advance of high resolution ultrasound, studies on noninvasive evaluation of the uterine cavity have dramatically increased. Many studies showed thicker endometrium on grayscale sonography in neoplastic endometrial lesions [8][9][10][11]. However endometrial thickening on TVS is a nonspecific finding, therefore secondary tests are usually required to reduce false positive results.…”
Section: Discussionmentioning
confidence: 99%
“…A few authors have studied the role Doppler indices of genital vessels in differentiation of premalignant and malignant endometrial lesions. Some reported Doppler ultrasound to be useful but others limited to the values [6,8,11,14,19,20]. The characteristics of endometrial and myometrial vascularization on Doppler sonography were then searched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por lo tanto existe una relación entre la resistencia de los vasos endometriales y la posibilidad de que este tejido tenga un componente maligno. A pesar de los aspectos teóricos y considerando de que existe un estudio demostrando una reducción de la resistencia de los vasos endometriales en pacientes con lesiones difusas, la contribución de la evaluación Doppler no mejora significativamente ni la sensibilidad ni la especificidad en la detección de hiperplasia o cán-cer endometrial, cuando éste es comparado con la medición endometrial realizada por ecografía transvaginal (8). Por lo tanto, la evaluación Doppler de la cavidad endometrial no tiene mayor contribución en el estudio de las pacientes peri y postmenopáusicas con sangrado uterino anormal.…”
Section: Métodos Basados En Imágenesunclassified